2022
DOI: 10.1113/jp283238
|View full text |Cite
|
Sign up to set email alerts
|

Physiological insight into the conserved properties of Caenorhabditis elegans acid‐sensing degenerin/epithelial sodium channels

Abstract: Acid sensing ion channels (ASICs) are members of the diverse family of degenerin/epithelial sodium channels (DEG/ENaCs). They perform a wide range of physiological roles in healthy organisms, including in gut function and synaptic transmission, but also play important roles in disease, as acidosis is a hallmark of painful inflammatory and ischaemic conditions. We performed a screen for acid-sensitivity on all 30 subunits of the C. elegans DEG/ENaC family using Two-Electrode Voltage Clamp (TEVC) in Xenopus oocy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 123 publications
2
24
0
Order By: Relevance
“…C. elegans ACD-2 is a close relative of ACD-1, ACD-5, and FLR-1 (Fig. 1 ) and has recently been reported to be activated by protons with low sensitivity (pH 50 = 5.0) 55 . Belonging to the same clade is Drosophila PPK1, which is expressed in multidendritic sensory neurons, and has also been reported to sense acid 58 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…C. elegans ACD-2 is a close relative of ACD-1, ACD-5, and FLR-1 (Fig. 1 ) and has recently been reported to be activated by protons with low sensitivity (pH 50 = 5.0) 55 . Belonging to the same clade is Drosophila PPK1, which is expressed in multidendritic sensory neurons, and has also been reported to sense acid 58 .…”
Section: Discussionmentioning
confidence: 89%
“…TadNaC2 is also activated by protons with low sensitivity (pH 50 = 5.1) 29 and TadNaC6 is a constitutively open channel which is modulated by alkaline pH 15 . While Del-9 is also activated by protons with low sensitivity (pH 50 = 4.3) 55 , the activating stimulus of Del-10 is currently unknown. It is therefore tempting to conclude that the last common ancestor of Cnidaria, Placozoa and deuterostomes had a proton-sensitive DEG/ENaC, which was at the base of this subclade, and that multiple duplication events occurred during the later evolution of these lineages, including independent gene losses in some protostomes and medusozoans.…”
Section: Discussionmentioning
confidence: 99%
“…The DEG/ENaC channels show a diversity in ion selectivity and permeability; while many are Na + -selective, some are also permeable to K + or Ca 2+ , and some invertebrate members exhibit a greater relative selectivity for other cations than Na + (Dürrnagel et al 2012;Fechner et al 2021;Kaulich et al 2022b;Wang et al 2008;further reviewed in Vallee et al 2021).…”
Section: Structural Insights Into Deg/enac Functionmentioning
confidence: 99%
“…This includes vertebrate ASICs Coric et al 2005;Springauf & Grunder, 2010;Waldmann et al 1997b;Zhang & Canessa, 2002), likely Drosophila Ppk1 (Boiko et al 2012) (although this has not been confirmed by heterologous expression), C. elegans ASIC-1 and DEL-9 (Kaulich et al 2022b) and cnidarian, brachiopod, phoronid, annelid, xenacoelomorpha and hemichordate representatives (Aguilar-Camacho et al 2022;Martí-Solans et al 2022). The other subgroup of the acid-activated channels includes the human ENaCs (Collier & Snyder, 2009;Ji & Benos, 2004) and C. elegans ACD-2 (Kaulich et al 2022b), which show some basal activity that can be blocked by amiloride and enhanced by acidic extracellular pH. However, this may not necessarily infer basal activity in vivo, depending on the physiological pH environment that the channel encounters, and could also be because heterologous expression rarely reflects the physiological environment.…”
Section: Acid-sensing Members Found Across Phylamentioning
confidence: 99%
See 1 more Smart Citation